PENGARUH RASIO PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP PERTUMBUHAN LABA: (Studi pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Irma Yuliani; Rizca Puspita Devi (Economicus : Jurnal Ekonomi dan Manajemen, 2024)
A number of nations, including Indonesia, saw the effects of the worldwide economic downturn that started in 2020 with the horrific COVID-19 epidemic. As a result, many businesses saw a drop in sales and a corresponding decrease in profitability. This study aims to examine the relationship between the Solvency Ratio (DER), the Current Ratio (CR), and the Return on Equity (ROE) as they pertain to food and beverage firms listed on the Indonesia Stock Exchange and their profit growth. This research used financial records and data acquired via deliberate sampling from food and beverage firms listed on the IDX from 2018 to 2022. Profit growth is significantly impacted by return on equity (ROE), as shown in the analysis. It would seem that the growth in profits is unaffected by either the Current Ratio (CR) or the Debt to Equity Ratio (DER). Profit growth for the food and beverage sectors listed on the Indonesia Stock Exchange from 2018 to 2022 is influenced by Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER).